Management and prevention of acute bleedings in the head and neck area with interventional radiology. Issue 1 (December 2016) - Storck, Katharina; Kreiser, Kornelia; Hauber, Johannes; Buchberger, Anna-Maria; Staudenmaier, Rainer; Kreutzer, Kilian; Bas, Murat
Abstract Background The Interventional Neuroradiology is becoming more important in the interdisciplinary treatment of acute haemorrhages due to vascular erosion and vascular tumors in the head and neck area. The authors report on acute extracranial haemorrhage in emergency situations but also on preventive embolization of good vascularized tumors preoperatively and their outcome. Methods Retrospective analysis of 52 patients, who underwent an interdisciplinary approach of the ORL Department and the Interventional Neuroradiology over 5 ½ years at the Department of Otorhinolaryngology, Klinikum Rechts der Isar, Technical University of Munich, Germany. Their outcome was analysed in terms of success of the embolization, blood loss, survival rate and treatment failures. Results 39/52 patients were treated for acute haemorrhage. Twenty-five of them attributable to vascular erosion in case of malignant tumors. Affected vessels were the common carotid artery as well as its internal and external parts with branches like the ascending pharyngeal, the facial and the superior thyroid artery. Altogether 27/52 patients were treated for malignant tumors, 25/52 were attributable to acute haemorrhage due to epistaxis, after tonsillectomy, benign tumors and bleeding attributable to inflammations. Treatment of all patients consisted either of an unsuccessful approach via exposure, package of the bleeding, electrocoagulation or surgical ligature followed by embolization or the primary treatment via interventional embolization/stenting. Conclusions The common monitoring of patients at the ORL and interventional neuroradiology is an important alternative especially in the treatment of severe acute haemorrhage, following vascular erosion in malignant tumors or benign diseases. But also the preoperative embolization of good vascularized tumors must be taken into account to prevent severe blood loss or acute intraoperative bleeding.